To the question of aggregative stability of latex stabilized by the mixture of non-ioniq and anionic surfactants - T. S. Solovieva; N. N. Ivanova (Тонкие химические технологии)
The colloid properties of styrene-butadiene latex stabilysed by the mixture of anionic alkylsulphonat (AS) and non-ionic oxiethylated fat alcohole (OC-20) were investigated. Addition of little amounts (less than 0,2 mol. Part) of AS into the mixture was founed to lead to the non-additive changes in particle sizes, influence the thickness of adsorbtion layers, Z-potencial and latex viskosity. It was shown that an agregative stability of the latex in the presents of different destabilizating factors (addition of electrolites, increasing of temperature, freezing, mechanical stiring) can be controlled, depending of their practical use, by changing the emulsifier mixture composition. For example, by changing the AS content in the composition one can reach the different thermosensibility of latex.